2017
DOI: 10.5005/jp-journals-10019-1187
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Intercanthal, Interpupillary, Interalar, and Intercommissural Distance with the Mesiodistal Width of the Maxillary Anteriors: An in vivo Study

Abstract: Aim This study was conducted for the selection of artificial teeth for edentulous patients with the help of extraoral facial measurement. Materials and methods The intercanthal distance, interpupillary distance, interalar distance, intercommissural distance, and width of maxillary six anteriors from a total of 250 subjects were measured clinically. The measurements were made with the help of a digital caliper. Student's t-test was used to find the significance of parameters between male and female. Pearson c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Since the repeatability and consistency of the studies based on these stable measurements are high, these measurements are used by studies, especially in orthodontic and prosthetic dentistry. The in vivo study by Bangar et al, which was conducted to select artificial teeth for patients with missing anterior teeth via extraoral facial anthropometric measurements, established a high degree of positive correlation between IPD, intercanthal distances (ICDs), and ICW, which was observed for both sexes (24). In support of these findings, Tripathi et al also found ICD and IPD to be correlated with ICW (10).…”
Section: Discussionmentioning
confidence: 91%
“…Since the repeatability and consistency of the studies based on these stable measurements are high, these measurements are used by studies, especially in orthodontic and prosthetic dentistry. The in vivo study by Bangar et al, which was conducted to select artificial teeth for patients with missing anterior teeth via extraoral facial anthropometric measurements, established a high degree of positive correlation between IPD, intercanthal distances (ICDs), and ICW, which was observed for both sexes (24). In support of these findings, Tripathi et al also found ICD and IPD to be correlated with ICW (10).…”
Section: Discussionmentioning
confidence: 91%